The brain drain from developing countries - Frédéric Docquier (IZA World of Labor, 2014)
The proportion of foreign-born people in rich countries has tripled since 1960, and the emigration of high-skilled people from poor countries has accelerated. Many countries intensify their efforts to attract and retain foreign students, which increases the risk of brain drain in the sending countries. In poor countries, this transfer can change the skill structure of the labor force, cause labor shortages, and affect fiscal policy, but it can also generate remittances and other benefits from expatriates and returnees. Overall, it can be a boon or a curse for developing countries, depending on the country's characteristics and policy objectives.
Keywords: F22; O1; O15; 330; migration; brain drain; development; growth